Pendidikan Multikultural Berlandaskan Pancasila dan Semboyan Bhineka Tunggal Ika - Duanto, Yayan Bagus; Meida, Elsa Farameida; Saputri, Rizka Maulina; Ediansyah, Pemi; Febriana, Bunga (TSAQOFAH, 2022)
Multicultural education as a means to achieve progressive educational goals where multicultural education teaches something related to history and culture. So that it can encourage the progress of the nation, in this learning students are taught and shown about various cultures, not only culture but also about national unity and integrity. As a teacher, especially a lecturer in multicultural education, it is very important in the world of education. Likewise with students who must be active to take part in the learning. Multicultural education is a provision to carry out existing rules in society, such as mutual respect and respect between fellow human beings. The nation will progress if education is carried out properly and correctly in accordance with existing rules and regulations, through multicultural education this will encourage progress and harmony. And this research uses library research methods or literature, by looking for information relating to multicultural education as a driver of the nation's progress. As for the implementation, researchers need data sources related to the title of our research that can support the success of the research including books, journals, articles and some other literature.